EFFECIENCY OF COPPER NANOPARTICLES COATED MINT AS ANTI-FUNGAL AGAINST SAPROLEGNIASIS DISEASE IN COMMON CARP - Alwash, Sarab W.; Al-Faragi, J. K.; Al-Saadi, Tagreed M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The present study was aimed to find out the efficacy of M-CuNPs, mint, and CuSO4 in controlling saprolegniasis in common carp. The efficacy of Cu-NP which prepared by using chemical method was examined. 120 fish of weight 80±10g were groups divided into six replications (10 fish/replicate) and the groups were treated as follows: (C-) health without any infection and without treatment, (C+) infected and without treated, (T1 and T2) The fish were infected with the fungus and treated with M-CuNPs at concentrations 20, and 10 mg/l respectivly.T3: fish infected with fungus and treated with copper sulfate at concentration 0.5mg/l. T4: Infected fish were treated at a concentration 100 mg/L of mint. After 14 days of treatment, samples were collected from fish for study the histopathological changes. The copper nanoparticles treatment, 20 mg/l showed the highest survival rate (85%). The survival rate of the control group (C+)(50%). Histopathological studies revealed a significantly increased (p<0.05) percentage of gill epithelial proliferation and epithelial lifting in fish from nanoparticles groups relative to C(+) and C(-). Copper nanoparticles appear to be a good disinfectant against Saprolegnia infection at the dose of 20 mg/l.